Papanicolaou test and human papillomavirus: women’s knowledge analysis - Pereira, Rita de Cássia Sá; Amaral, Sãmyla de Cassia dos Reis; Gato, Thaís Zahlouth Serique; Rodrigues-Antunes, Symara; Lima, Sergio Beltrão de Andrade; Guerra, Sylvia de Fátima dos Santos; Feio, Danielle Cristinne Azevedo (Revista Uningá, 2022)
Human papillomavirus (HPV) is the most common sexually transmitted infection and occurs worldwide, especially in underdeveloped countries. It’s also strongly associated with cervical cancer. Papanicolaou test is an important tool for early diagnosis of such cancer. Hence, our objective is to evaluate women's knowledge about Pap smear, as well as about HPV transmission and clinical manifestations. This literature integrative review used the following research platforms: PubMed/Medline, SciELO and Virtual Health Library (BVS). Among the articles analyzed there were a total of 7,441 women, which mean age was over 16 years. Twenty percent of those had only high school education. Regarding knowledge about HPV, only 22% of the participants knew about it and 27% reported knowing about the Papanicolaou exam. It is concluded that socioeconomic factors are extremely relevant because they influence the incidence of HPV in society, emphasizing that knowledge about the Pap test and its purpose directly influences women’s acceptance to perform it.